Nutritional and antioxidative properties of underutilized Ziziphus mauritiana L. (bidara) for nutraceutical potential - Mohd Jailani, Fatin Nor Amirah (2021)
Nowadays, researchers around the globe are extensively searching for potential safe alternative drugs and antioxidant. The need for this alternative natural resource is due to the harmful side effects of current commercial synthetic drugs and antioxidant. The underutilized plant might be the key to discovering the presence of potential bioactive compounds for medicinal purposes or nutraceutical products. However, due to the scarcity of information and lack of study on many underutilized plants, the potential antioxidants compound remains undiscovered. Ziziphus mauritiana is one of Malaysian underutilized plant which had been used locally as traditional treatments and also for Islamic practises. This plant is believed to have good nutritional content and carries antioxidative properties. Thus, this study is carried out to investigate the nutritional composition and physicochemical value of Z. mauritiana extracts associated with the antioxidant capacity of the different extraction solvents. The nutritional composition of Z. mauritiana leaves, fruit and seed were determined using proximate analysis. The physicochemical properties of Z. mauritiana leaves and fruit were measured based on their pH value, total acidity (TA) and total soluble solid content (TSS) while antioxidant capacity was analyzed using TPC, TFC, FRAP and DPPH assays. Based on the results, leaves showed the highest percentage of ash (9.06%) and crude protein (14.59%) while the moisture content (88.32%) was found the highest in fruit. The crude fiber (48.12%), fat (1.89%), carbohydrate (63.24%) and energy (411.61 kJ) were the highest in the seed. The results also showed that Z. mauritiana fruit had a higher value of TSS (11.70°Brix) and TA (0.32%) than the leaves while the pH of the leaves (5.47) was higher than fruit (4.77). The phytochemical compound of squalene (46.69%) in leaves, 5-hydroxymethylfurfural (35.04%) in fruit and conipheryl alcohol (21.45%) in seed were the major compounds found using GC-MS analysis. The antioxidant capacity of Z. mauritiana in different solvent extracts showed that the highest TPC, TFC and FRAP value was found in leaves water extract (287.71 mgGAE/g), in fruit water extracts (119.75 mgQAE/g) and leaves acetone extract (10.06 mgFe/g) respectively. While the strongest free radical scavenging activity against DPPH was shown in the leaves water extract (4.02 μg/ml). According to principal component analysis (PCA), flavonoid compound has shown a significant positive correlation with ferric reducing power by 0.760 while the extracts can be classified into three distinctive groups of potential phenolic, flavonoid and weak scavenging activity against DPPH. Thus, the underutilized plant of Malaysian Z. mauritiana has the potential to be used as an alternative source of nutraceutical product.